2019
DOI: 10.1596/1813-9450-8845
|View full text |Cite
|
Sign up to set email alerts
|

Labelled Loans, Credit Constraints and Sanitation Investments

Abstract: Credit constraints are considered to be an important barrier hindering adoption of preventive health investments among low-income households in developing countries. However, it is not obvious whether, and the extent to which, the provision of labelled micro-credit-where the loan is linked to the investment only through its label-will boost human capital investments, particularly when it is characterised by other attractive attributes, such as a lower interest rate. This paper studies a cluster randomised cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Moreover, it provides confirmatory evidence to the assertion that insurance increases asset holding by circumventing asset depletion which could result from selling critical assets as a risk‐coping mechanism (Chetty & Looney, 2006). In addition, the findings suggesting that formal credit increased asset holding corroborated studies by Augsburg et al (2018) and Doss et al (2020). This indicated that access to formal credit such as credit cards or bank loans could improve the welfare of consumers through asset accumulation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, it provides confirmatory evidence to the assertion that insurance increases asset holding by circumventing asset depletion which could result from selling critical assets as a risk‐coping mechanism (Chetty & Looney, 2006). In addition, the findings suggesting that formal credit increased asset holding corroborated studies by Augsburg et al (2018) and Doss et al (2020). This indicated that access to formal credit such as credit cards or bank loans could improve the welfare of consumers through asset accumulation.…”
Section: Discussionsupporting
confidence: 87%
“…In summary, various theories discussed above suggest that the use of financial services including insurance, credit and savings is associated with increased asset holding. This has been confirmed by Augsburg et al (2018), Doss et al (2020), Ibrahim (2020), Kwarteng-Amaning and Sarfo-Mensah (2019) and Lee et al (2017), who showed that various channels of financial inclusion are associated with asset accumulation. Based on the theoretical prediction and empirical literature, we establish the following hypothesis: Hypothesis 1.…”
Section: Financial Inclusion Association With Asset Accumulationmentioning
confidence: 73%
See 2 more Smart Citations
“…But reassuringly, other studies have found the same linkage. For example, three studies of Indian WSS microfinance lending programs found that they increased toilet ownership by 2.64% [5], 9% [6] and 12.4% [7] respectively.…”
Section: Catalytic Creditmentioning
confidence: 99%